DESIGN OF AUTOMATED CONTROL SYSTEMS IN TELECOMMUNICATION ELECTRICAL SUPPLY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
To solve the problem of designing automated control systems in telecommunications power supply, it is necessary to develop design principles and methods based on morphological analysis and analysis of technical solutions. When creating an algorithm of automated design systems, it is necessary to create a database based on the technical characteristics of the modern power supply system and operational data of production devices.